A performance of the realities and illusions of Filipino living statues (2014)
Filipino performers have become fascinated with living-statue performance in the recent decades. Many of them today can be seen performing as living statues in various public places especially in the metropolitan areas, and during special events such as company launch and anniversaries. According to the X-tatu, the pioneering group of living statues in the Philipoines as they claim to be, the number of living statue performing groups in the country will continue to grow in the coming years. This is mainly because of the promise of a job in living-statue performance where the Filipino performers can get good money for their families. Always attached to this promise however, are a series of challenges they have to go through before, during, and after their performance. Difficulties that, according to the X-statu, rip off their humanness at certain points. To sustain themselves through these difficulties, aside from their constant motivation of having to fulfill their major responsibility of providing for their families, the Filipino living statues create certain illusions. These illusions become their saving factor in a performance, or a job, that is the living-statue performance, where there is nothing left for themselves but feelings of being constantly alienated and/or of losing their self-worth.
Keywords: living statue